THE INFLUENCE OF SELF-EFFICACY AND INTERNAL LOCUS OF CONTROL ON SELF-DEVELOPMENT MOTIVATION THROUGH WOMEN'S VIOLENCE PREVENTION TRAINING AT THE WOMEN'S EMPOWERMENT AND CHILD PROTECTION SERVICE OF JAYAPURA REGENCY - Mebri, Tresia Erselina Heni; Megawaty, Megawaty; Anshar, Muh. Ashary (International Journal of Multidisciplinary Research and Literature, 2025)
The purpose of this study was to determine the effect of Self-Efficacy and Internal Locus of Control on Self-Development Motivation through Women's Violence Prevention Training at the Women's Empowerment and Child Protection Service of Jayapura Regency. This study was quantitative. The population in this study were female participants who had participated in women's violence prevention training activities with a sample size of 100 respondents determined using the Slovin formula. Data collection in this study used a questionnaire. The data processing technique used in this study was SEM-PLS with the Smart PLS 3.0 application with Convergent Validity, Discriminant Validity, Composite Reliability and Hypothesis Testing. The results of this study indicate that self-efficacy and internal locus of control have a significant positive effect on women's violence prevention training. Self-efficacy has a significant positive effect on self-development motivation, while internal locus of control has a positive but insignificant effect on self-development motivation. Women's violence prevention training has a significant positive effect on self-development motivation. Self-efficacy and internal locus of control have a significant positive effect on self-development motivation through women's violence prevention training.